Parent Perspectives on COVID-19 Vaccination and the Resumption of Face-to-Face Classes - Bascara, Faith Cecille A. (Animo Repository, 2023)
Not all fully vaccinated students attended their face-to-face sessions during the shift of learning modality, from full online to limited face-to-face. Hence, this research aimed to answer the following questions: 1) What are the parents’ current outlook on face-to-face classes in light of the pandemic?; 2) What aspects were considered in the decision of parents to allow or disallow their child/ren to return to face-to-face learning modality?; and 3) How did the parents view the COVID-19 vaccine with regard to the security of their child/ren? A total of 10 parents of 12th grade Senior High School students from National University - Mall of Asia were selected as participants through purposive sampling to answer 10 questions through interview or questionnaire, depending on their availability. We found out that: a) parents were uncertain about the resumption of face-to-face classes, admitting that they are still protective of their children; b) parents were in favor of the face-to-face classes because of its academic effectiveness; c) most are still concerned with the presence of the virus; d) half of the parents supported the vaccination, with their decision set prior to the implementation of hybrid learning. The researchers have related these findings and formulated conclusions to the study’s theoretical framework through Gestalt psychology: “individual's behavior is the final comprehensive product of their current environment and how individuals view it.” Therefore, the parents’ positive perceptions of the COVID-19 vaccination and limited face-to-face classes show how the Philippines progressed, especially with the successful implementation of DepEd’s modality shift.